Family study of bipolar disorder with comorbid anxiety disorder points to THSD7A with possible role of parent‐of‐origin effect - Hiroaki Maki; Naomi Sakai; Muneko Kataoka; Kumiko Fujii; Yuki Kageyama; Takashi Hayama; Koji Matsuo; Masaki Nishioka; Tadafumi Kato (PCN Reports)
Abstract Aim The aim of this study was to provide new insights into the genetics of bipolar disorder (BD) by analyzing BD comorbid with anxiety disorders. Methods Structured interviews were conducted with BD patients and their parents. Cases were classified into those with comorbid anxiety spectrum (AS) and those without. The family history of patients with BD with comorbid AS was assessed. Focusing on parent‐of‐origin effects and genomic imprinting from the results, imprinted genes and tested single nucleotide polymorphisms (SNPs) in the identified genes were investigated for an association with BD by transmission disequilibrium test (TDT) using published whole‐exome sequencing data. Results The incidence of comorbid AS among all the patients with BD analyzed in this study was 39.6%. Patients with BD whose fathers had AS or mood disorders exhibited a significantly higher rate of AS. Among the known imprinted genes, two were associated with BD: THSD7A and CACNA1C. By pruning SNPs, six variants of the THSD7A exons and four variants of the CACNA1C exons were included in the analysis. Among these, one variant of THSD7A, rs2074603, showed over‐transmission from parents to patients with BD. Furthermore, it was nominally significant only for fathers when TDT was performed separately for fathers and mothers. Conclusion THSD7A may play a role in BD with parent‐of‐origin effects. Further research is necessary to explore the mechanisms by which genomic imprinting is associated with BD. Clinical Trial Registration: N/A.